Does the financial system support economic growth in times of financialisation? Evidence for Portugal - Barradas, R. (2020)
This paper conducts a time series econometric analysis in order to examine empirically the relationship between the financial system and economic growth in Portugal from 1977 to 2016. The Portuguese financial system has experienced a strong wave of privatisations, liberalisations and deregulations since the adhesion of Portugal to the European Economic Community in 1986, which has not favoured a sustained path of strong economic growth since then. The paper estimates a linear growth model and a non-linear growth model, which includes four proxies for the financial system (money supply, credit, financial value added and stock market capitalisation) and four further control variables (inflation, government consumption, trade openness and education). The paper finds a negative linear relationship between the banking system and Portuguese economic growth, a positive linear relationship between the stock markets and Portuguese economic growth, a concave quadratic relationship between the banking system and Portuguese economic growth, and a convex quadratic relationship between the stock markets and Portuguese economic growth. This suggests that Portuguese policy makers should canalise efforts to decrease the importance of banking system and to increase the importance of stock markets in order to support more robust economic growth in the coming years.